Zeolite as an Adsorbent Reduces Ammoniacal Nitrogen and COD in Rubber Processing Industry Efuents - Amir Detho, Amir Detho; Abdul Kadir, Aeslina; Rosli, Mohd Arif (Springer, 2023)
The rubber industry generates wastewater containing with elevated concentrations of organic compounds, suspended particulates, ammonia, colorants, and other impurities. The objective for this study is to investigate the efcacy of zeolite (ZEO) in reducing ammoniacal nitrogen (NH3-N) and chemical oxygen demand (COD) levels in efuents from the rubber industry. Samples were collected directly from a manufacturer’s discharge point. The study examined the efects of diferent factors, such as pH, dosage, retention time, and shaken speed. The optimal conditions for NH3-N and COD removal were found at a pH of 7, using 4.0 g of the adsorbent, agitated at 150 rpm for a retention period of 120 min. The pollutant removal efciency achieved around 85% across most batch experiments. The Langmuir model best described the experimental results, with R-squared values of 0.9983 and 0.9979 for NH3-N and COD respectively. Meanwhile, the pseudo-second order (PSO) kinetics model provided the closest ft for equilibrium studies, with R-squared values between 0.9988 and 1.000 for 90% of the investigations. Further studies are suggested to investigation zeolite’s efcacy in removing other contaminants, such as TDS, Zn, Fe, and Cu, from rubber industry wastewater.